The Effectiveness of E-Modules Based on Cognitive Load Theory on Learning Outcomes and Cognitive Load of Vocational High School Students - Fania Komala Sari; Rizki Hikmawan; Andriansyah Setiawan (Journal of Educational Sciences, 2026)
The goal of this project is to create an e-module with cognitive load management in mind and assess how it affects vocational high school students' learning results. The study uses a pre-experimental experimental design of the one-shot case study type and a descriptive quantitative methodology. A cognitive load questionnaire was used to quantify intrinsic, extraneous, and relevant cognitive load, and a post-test was used to determine learning outcomes. A one-sample binomial test and the Shapiro Wilk normality test were used for data analysis. A binomial test with a significance threshold of 0.035 (<0.05) was employed since the results demonstrated that the data were not normally distributed, suggesting that the e-module design had an impact on student learning outcomes. According to descriptive analysis, the average student learning outcome of 83.33 is classified as "good." Furthermore, extraneous cognitive load fell into the "very low" category (mean = 1.70), intrinsic cognitive load into the "low" category (mean = 2.48), and germane cognitive burden into the "very high" category (mean = 3.44). In conclusion, the findings indicate that the e-module is associated with structured learning and favorable cognitive load conditions among students, but the results remain descriptive and cannot be interpreted as causal evidence.